Design thinking: catalysing change in the educational ecosystem – a framework for future challenges - Anders Berglund (Design Science)
Universities face a critical crossroads, in need of swift, targeted, and efficient actions to address future challenges. This necessities a strategic approach to updating and assessing engineering design education. Efforts to improve teaching and learning require systematic change in many universities, yet research on structuring such change is scarce. Few studies have combined a systems perspective with a functional operational level. This research embeds design thinking to structure to isolated actions. Drawing from an extensive literature review of educational change frameworks and several illustrative cases, this article demonstrates the potential of design-driven change. It highlights how dynamic interrelations can facilitate educational transformations across diverse academic levels. By presenting an educational ecosystem as a framework for systematic educational change, design thinking functions as a catalyst for educational transformation. The article also presents case findings that strengthen supportive actions ingrained in existing change research frameworks connecting, them to a transparent approach for sustainable and careful decision-making.